Enhancing Mesenchymal Stromal Cell Potency: Inflammatory Licensing via Mechanotransduction - Skibber, Max A.; Olson, Scott D.; Prabhakara, Karthik S.; Gill, Brijesh S.; Cox, Charles S. (Frontiers in Immunology, 2022)
Mesenchymal stromal cells (MSC) undergo functional maturation upon their migration from bone marrow and introduction to a site of injury. This inflammatory licensing leads to heightened immune regulation via cell-to-cell interaction and the secretion of immunomodulatory molecules, such as anti-inflammatory mediators and antioxidants. Pro-inflammatory cytokines are a recognized catalyst of inflammatory licensing; however, biomechanical forces, such as fluid shear stress, are a second, distinct class of stimuli that incite functional maturation. Here we show mechanotransduction, achieved by exposing MSC to various grades of wall shear stress (WSS) within a scalable conditioning platform, enhances the immunomodulatory potential of MSC independent of classical pro-inflammatory cytokines. A dose-dependent effect of WSS on potency is evidenced by production of prostaglandin E2 (PGE2) and indoleamine 2,3 dioxygenase 1 (IDO1), as well as suppression of tumor necrosis factor-α (TNF- α) and interferon-γ (IFN-γ) production by activated immune cells. Consistent, reproducible licensing is demonstrated in adipose tissue and bone marrow human derived MSC without significant impact on cell viability, cellular yield, or identity. Transcriptome analysis of WSS-conditioned BM-MSC elucidates the broader phenotypic implications on the differential expression of immunomodulatory factors. These results suggest mechanotransduction as a viable, scalable pre-conditioning alternative to pro-inflammatory cytokines. Enhancing the immunomodulatory capacity of MSC via biomechanical conditioning represents a novel cell therapy manufacturing approach.